Topologies generated by probabilistic quasi-pseudo-metrics - Cho, Yeol Je (Tamsui Oxford Journal of Mathematical Sciences)
In this paper, we give the properties of some topological spaces generated by Pqp-metrics and we study properties (separation axiom) of a bitopological space (X, T(subscript P), T(subscript Q)) generated by a Pqp-metrics.